2008
DOI: 10.1097/01.prs.0000302456.02109.04
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Submuscular Resorbable Mesh for Correction of Severe Postpregnancy Musculoaponeurotic Laxity: An 11-Year Retrospective Study

Abstract: The release and plication of the posterior rectus sheath associated with the use of submuscular resorbable mesh is a long-lasting and reliable procedure in multiparous women with severe myoaponeurotic laxity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Experimental plication methods used to augment tissue integrity and promote adequate wound healing included application of resorbable mesh [11,12], self-locking knots, additional stitches into the aponeurosis [13], reinforced tension line [14], and the placement of two layers of sutures [2,15]. Moreover, other studies revealed that a suture length to wound length ratio of 4:1 (or even 6:1) decreased the incidence of incisional hernia in comparison to smaller ratios [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental plication methods used to augment tissue integrity and promote adequate wound healing included application of resorbable mesh [11,12], self-locking knots, additional stitches into the aponeurosis [13], reinforced tension line [14], and the placement of two layers of sutures [2,15]. Moreover, other studies revealed that a suture length to wound length ratio of 4:1 (or even 6:1) decreased the incidence of incisional hernia in comparison to smaller ratios [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of moderate to severe diastasis recti, a retrorectus repair can be considered. 25,26 With this technique, an anterior paramedian incision is made adjacent to the lateral aspect of the linea alba extending from the xiphoid to the pubic bone. The medial aspect of the rectus abdominis muscle is undermined preserving the vascularity and laterally based innervation.…”
Section: Retrorectus Repair With Meshmentioning
confidence: 99%
“…Concernant les données opératoires, nous avons répertorié : la durée opératoire, le volume de lipoaspiration antérieure dans les deux groupes et le volume de lipoaspiration postérieure dans le groupe LAP2P [3]. Le retentissement sur la numération sanguine a été évalué par la mesure de l'hémoglobine préopératoire et postopératoire à j1.…”
Section: Méthodeunclassified